Molecular Characterization of IgA- and/or IgG-Switched Chronic Lymphocytic Leukemia B Cells - Matolcsy, András (Blood, 1997)
The immunoglobulin (Ig) variable region (V) genes expressed by IgM chronic lymphocytic leukemia (CLL) B cells display little or no somatic mutations. However, preliminary findings have shown that Ig V genes of IgA and IgG CLLs may be somatically mutated, suggesting that isotype-switched CLLs may represent a “subtype” of the disease. To investigate the degree and nature of somatic mutations and the role of antigen (Ag) in the clonal selection and expansion of isotype-switched CLLs, and to determine whether specific oncogene or tumor suppressor gene mutations are associated with isotype-switched CLLs, we analyzed the expressed Ig V(H) gene, bcl-1 and bcl-2 proto-oncogene, and p53 tumor suppressor gene configurations of 3 IgA-, 1 IgG-, and 1 IgA/IgG-expressing CLLs. These isotype-switched CLL B cells expressed surface HLA-DR, CD19, CD23, and CD5, and dis played no alterations of the bcl-1 and bcl-2 oncogenes and the p53 tumor-suppressor gene. The cDNA V(H)-D-J(H) gene sequence was joined with that of the Cα gene in the B cells of the three IgA CLLs, and with that of the Cγ gene in the IgG CLL B cells. In the IgA/IgG-coexpressing CLL B cells, identical V(H)-D-J(H) cDNA sequences were spliced to either Cα or Cγ genes. In all five CLLs, the pattern of Cμ DNA probe hybridization to the digested genomic DNAs was consistent with deletion of the Cm exon from the rearranged Ig gene locus, suggesting that these CLL B cells had undergone DNA switch recombination. In one IgA CLL, the expressed V(H) gene was unmutated. In all other class-switched CLLs, the Ig V(H) segment gene was mutated, but the point mutations were not associated with intraclonal diversification. In one IgA and in the IgA/IgG-coexpressing CLL, the nature and distribution of the mutations were consistent with Ag selection. These findings suggest that IgA- and/or IgG-expressing CLLs represent, in their V(H) gene structure, transformants of B cells at different stages of ontogeny. They also suggest that Ag may play a role in the clonal selection of some of these isotype-switched leukemic cells, but bcl-1 and bcl-2 oncogene rearrangements and p53 tumor suppressor gene mutation are not associated with the pathogenesis of isotype-switched CLLs.